Shot Characteristics Based on Match Period in Elite Table Tennis Matches - Wang, Jie (Frontiers in Psychology, 2021)
This study aimed to compare the shot characteristics amongst different match periods in table tennis matches. For the shot characteristics of position, type, placement and efficacy, 13 men’s singles matches comprising 72 sets from a round of 16 to the final in the 2019 World Table Tennis Championships were selected for notational analysis. Kruskal–Wallis and Mann–Whitney tests were conducted to quantify the differences in various categories of each variable amongst the initial, intermediate and ending match periods. There are no significant differences in each distribution between initial and intermediate periods. From intermediate to ending periods, significant decreases were found in chop type (p < 0.01) and middle long placement (p < 0.01), whereas a significant increase was found in backhand half placement (p < 0.05). By comparing the initial and ending periods, significant decreases were found in middle backhand turn position (p < 0.05), middle long placement (p < 0.01), chop (p < 0.01) and poor shots (p < 0.05). Therefore, shot characteristics in table tennis matches are match period related, and the main differences existed between the beginning and the ending period. From initial to ending period, the frequency of applying the middle long placements is decreasing. At the end of every set, the players adopted a safe stroke position, performed offensive stroke types and deployed flexible stroke placement. Results suggested that coaches can establish different scenarios on the basis of varying match periods for players’ training.